Autonomic regulation of heart rate during specific dynamic action associated with digestion in the bullfrog Lithobates catesbeianus - Claesson, Debora [UNESP]; Abe, Augusto Shinya [UNESP]; Wang, Tobias [UNESP] (Soc Brasileira Zoologia, Univ Federal Parana, 2015)
Feeding causes a substantial rise in the aerobic metabolism of all vertebrates, which is met by a rise in heart rate to secure adequate oxygen delivery, as well as intestinal nutrient absorption and transport between organs. To study the autonomic regulation of this postprandial tachycardia in an amphibian, we placed arterial catheters in individuals of the bullfrog, Lithobates catesbeianus (Shaw, 1802), to measure their blood pressure and heart rate. Heart rate in experimental subjects increased from a fasting value of 42.5 +/- 2.5 to 52.5 +/- 1.6 and 57.5 +/- 2.1 min(-1) at 24 and 33 hours, respectively, after meals that corresponded to 5% of their body weight. Using an infusion of atropine and propranolol, we demonstrated that part of the postprandial tachycardia can be ascribed to a progressive decrease in parasympathetic tone (26 +/- 5% in fasting frogs to 6 +/- 5% by 33 hours into digestion), whereas the sympathetic tone remained unaltered at approximately 20%. In addition to the withdrawal of vagal tone, digestion was also associated with an increase in the heart rate upon double-blockade (i.e., the combination of atropine and propranolol) from a fasting value of 44.5 +/- 0.9 to 50.8 +/- 1.9 min(-1) at 33 hours. This indicates that the postprandial tachycardia in frogs, as previously demonstrated for snakes, is partially governed by excitation of non adrenergic, non cholinergic (NANC) factors.
Keywords: Adrenergic; cholinergic; postprandial tachycardia